Supplement use by young athletes - McDowall, J. A. (Journal of Sports Science & Medicine, 2007)
This paper reviews studies of supplement use among child and adolescent athletes, focusing on prevalence and type of supplement use, as well as gender comparisons. Supplement use among adult athletes has been well documented however there are a limited number of studies investigating supplement use by child and adolescent athletes. A trend in the current literature revealed that the most frequently used supplements are in the form of vitamin and minerals. While health and illness prevention are the main reasons for taking supplements, enhanced athletic performance was also reported as a strong motivating factor. Generally, females are found to use supplements more frequently and are associated with reasons of health, recovery, and replacing an inadequate diet. Males are more likely to report taking supplements for enhanced performance. Both genders equally rated increased energy as another reason for engaging in supplement use. Many dietary supplements are highly accessible to young athletes and they are particularly vulnerable to pressures from the media and the prospect of playing sport at increasingly elite levels. Future research should provide more direct evidence regarding any physiological side effects of taking supplements, as well as the exact vitamin and mineral requirements for child and adolescent athletes. Increased education for young athletes regarding supplement use, parents and coaches should to be targeted to help the athletes make the appropriate choices.